2013
DOI: 10.1186/1471-2164-14-11
|View full text |Cite
|
Sign up to set email alerts
|

Double restriction-enzyme digestion improves the coverage and accuracy of genome-wide CpG methylation profiling by reduced representation bisulfite sequencing

Abstract: BackgroundReduced representation bisulfite sequencing (RRBS) was developed to measure DNA methylation of high-CG regions at single base-pair resolution, and has been widely used because of its minimal DNA requirements and cost efficacy; however, the CpG coverage of genomic regions is restricted and important regions with low-CG will be ignored in DNA methylation profiling. This method could be improved to generate a more comprehensive representation.ResultsBased on in silico simulation of enzyme digestion of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 49 publications
3
72
3
Order By: Relevance
“…6A) and a much smaller percentage (7%) mapped to gene promoters (promoters were defined as regions up to –5 kb from the transcription start site (TSS) of the gene). These results contrasted with human RRBS data where 32% of the investigated CpG sites were in promoters 43 . Fifty one percent of the CpG sites were distant, i.e., further than 5 kb upstream of the gene.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…6A) and a much smaller percentage (7%) mapped to gene promoters (promoters were defined as regions up to –5 kb from the transcription start site (TSS) of the gene). These results contrasted with human RRBS data where 32% of the investigated CpG sites were in promoters 43 . Fifty one percent of the CpG sites were distant, i.e., further than 5 kb upstream of the gene.…”
Section: Resultscontrasting
confidence: 95%
“…In contrast, a recent RRBS study on humans (MspI digested and size selection of 40–220 bp fragments) showed 47.5% and 19.5% of the investigated CpG dinucleotides were in core CpG island and CpG island shores respectively 43 . Our data indicate that the mapped CpG dinucleotides are more prevalent in CpG island shores of the zebrafish RR genome and less frequent in core CpG islands compared with the equivalent analysis in human.…”
Section: Resultscontrasting
confidence: 88%
“…SOX10 is broadly expressed in human normal adult tissues and fetal tissues. Previous studies present that SOX10 is frequently silenced by promoter CpG methylation in colorectal cancer, gastric cancer and ESCC cell lines (22)(23)(24). The expression status of SOX10 in ESCC in the report is consistent with our study that SOX10 was down-regulated in ESCC compared to normal controls through bioinformatics analysis and qRT-PCR validation.…”
Section: Discussionsupporting
confidence: 91%
“…The colon cell line pair (HCT116 and DNMT1/DNMT3B double knock-out (DKO)) provides us with a useful model system to identify key methylated cancer genes involved in colon tumorigenesis, which has been widely used by other researchers 18, 29, 30. Through methylome analysis of HCT116 and DKO pair cell line, we identified JPH3 as a methylated TSG candidate in colon cancer.…”
Section: Discussionmentioning
confidence: 99%